STRATEGIES FOR FUNDING BUSINESS EDUCATION FOR SUSTAINABLE SKILL ACQUISITION (Journal of the Management Sciences, 2024)
Business education has different strategies for its proper funding. Business education has as one of its aims, the empowerment of students with skills necessary to meet business challenges in our society in this digital era. One major challenge facing Business Education is inadequate funding to run the affairs of Business Education. Skill acquisition is the systematic and sequential development of skills that promotes efficiency and effectiveness. The paper examined the strategies for funding business education for sustainable skill acquisition. The concept of funding, business education, common features of business education, skill acquisition, relevance of skill acquisition in business education, means of financing business education for improved skill acquisition, benefits derived from skill acquisition in business education, challenges in funding business education for sustainable skill acquisition, and ways forward for funding business education for sustainable skill acquisition. Recommendations were made among others that the federal and state governments should adequately fund business education programme to overcome some of its challenges.
Keywords: Funding, Business Education and Sustainable Skills Acquisition